Utilization of Local Culture as A Tourism Marketing Instrument - Iswanto, Dedy; Irsyad, Ziqrurrahman; Istiqlal, Istiqlal (Aurora: Journal of Emerging Business Paradigms, 2025)
This study aims to explore the utilization of local culture as a tourism marketing instrument through a Systematic Literature Review (SLR) approach. The study was conducted by selecting literature from academic databases such as Scopus, DOAJ, and Google Scholar, using keywords such as “local culture,” “tourism marketing,” “destination branding,” and “cultural tourism” within the time span of 2014-2024. The results show that the integration of local culture in destination promotion significantly enhances tourist attraction and experience. However, challenges such as cultural commodification and overtourism need to be addressed to maintain cultural authenticity. The use of social media and digital technology plays an important role in increasing cultural visibility, but the potential for distortion in the delivery of cultural values remains an important issue. The involvement of local communities as custodians of cultural heritage proved essential in ensuring the sustainability of promotion balanced with the preservation of traditions. Therefore, future research is recommended to explore the social and cultural influences in maintaining the authenticity of local culture in tourism marketing..